What matters more for child health: A father's education or mother's education?. (June 2018) - Karki Nepal, Apsara
Highlights: A strong and direct relationship exists between the mother's education and child health. There is no direct relationship between the fathers education and child health. Results are robust across different specifications and sub-sample. There is no heterogeneity or interaction effects of rural/urban locations and the child's gender (boy/girl) on child health outcomes contrary to the general perception that a strong gender bias exists in favour of boys and that the rural location inherently disadvantages rural children vis-à-vis their urban counterparts with regard to health outcomes. Difference in health outcomes is Binder-Oaxaca decomposition indicates that the demographic characteristics, health environment, information, and economic factors are the observed factors that explain most of the difference in health outcomes. Abstract: This research examines the relationship between parental education and child health outcomes using the Nepal Living Standards Survey 2010/11. Controlling for a range of observable characteristics, we find that a mother's education has a positive and significant effect on child health outcomes. A higher level of a mother's education has a larger direct effect on child health outcomes but mother's education below 8th grade has no direct effect on child health regardless of the child's gender and the household's location once we control for potential pathways and district fixed effects. However, surprisingly, no statistically significant relationship subsists between a father's education and child health outcomes. In order to determine the exact gap between the health outcomes of children of mothers with higher versus lower education and the factors contributing to those gaps, we use the Blinder-Oaxaca decomposition method. This analysis shows that a healthy environment, access to information, and the demographic and economic characteristics of households are the major factors that explain most of the child health outcome gaps.